"Nature, " "Homer, " and "Shakespeare": Revisiting Pope and Wordsworth on How to Write Poetry. Issue 2 (3rd April 2017) - Jiang, Zhuyu
ABSTRACT: Both Alexander Pope (1688–1744) and William Wordsworth (1770–1850) proposed their own opinions about how to create poetry. As the representative poet of the school of Romanticism, William Wordsworth is supposed to revise and refine Pope's ideas, who is the representative of the schools of Neoclassicism and who came earlier than Wordsworth. Pope believed that there are rules and traditions in literary classics, and he emphasized the importance of learning about them and applying them in poets' creation to make the poetry just and conformed. Wordsworth, who came later, preferred the utmost and fluent expression of personal feelings to rigid adherence to rules and traditions. Yet, if we reexamine the two great critics' ideas about how to make poetry, we will find that both emphasize a synthesis of rules and feelings, for example Pope's "Nature" and "Homer, " and Wordsworth's "Nature" and "Shakespeare." This essay will reexamine critical works of both Pope and Wordsworth to illuminate how critics from different times give similar ideas about the synthesis of rules and feelings in the creation of poetry.